Therapeutic management of classic lichen planopilaris: a systematic review - Errichetti E; Figini M; Croatto M; Stinco G (Dove Medical Press, 2018)
Enzo Errichetti, Matteo Figini, Margherita Croatto, Giuseppe Stinco Department of Experimental and Clinical Medicine, Institute of Dermatology, University of Udine, Udine, Italy Abstract: Several treatment strategies have been proposed in classic lichen planopilaris (LPP), although no gold standard therapeutic approach has been recognized so far due to the variable and, sometimes, contradictory results reported in the literature, as well as due to the lack of guidelines and randomized controlled trials. In the present review, we sought to provide an updated overview on the treatment of classic LPP by analyzing the level of evidence of published studies, also proposing a possible therapeutic strategy according to the findings highlighted in this systematic review. Keywords: lichen planopilaris, management, therapy, treatment